The circadian rhythms regulated by Cx43-signaling in the pathogenesis of Neuromyelitis Optica - Xue, Huiru; Wu, Minghui; Wang, Yongle; Zhao, Yunfei; Zhang, Meini; Zhang, Hui (Frontiers in Immunology, 2023)
Neuromyelitis Optica (NMO) is an inflammatory demyelinating disease of the central nervous system (CNS). NMO manifests as selective and severe attacks on axons and myelin of the optic nerve and spinal cord, resulting in necrotic cavities. The circadian rhythms are well demonstrated to be a profound impact on cellular function, behavior, and disease. However, its molecular basis in NMO is unknown. In this study, we used an Aquaporin 4（AQP4） IgG-induced NMO cell model in isolated astrocytes. The NMO cell model was evaluated by the levels of glutamate, anterior visual pathway (AVP), and vasoactive intestinal peptide (VIP). We found that Bmal1 and Clock, two essential components of the circadian clock, were significantly decreased in NMO astrocytes, which were reversed by Cx43 activation (linoleic acid) or glutamate. Moreover, the expression levels of Bmal1 and Clock were also decreased by Cx43 blockade (TAT-Gap19) or glutamate receptor inhibition (DQP-1105). Furthermore, adenovirus-mediated Bmal1 knockdown by shRNA (Ad-sh-Bmal1) dramatically decreased the levels of glutamate, AVP, and VIP, and significantly down-regulated the protein level of Cx43 in NMO astrocytes with Cx43 activation (linoleic acid) or glutamate treatment. However, Bmal1 knockdown did not alter these levels in normal astrocytes with Cx43 blockade (TAT-Gap19) or glutamate receptor inhibition (DQP-1105). Collectively, these results suggest that Cx43-glutamate signaling would be a critical upstream regulator that contributes to the NMO induced rhythmic damage in SCN astrocytes.